Sangka-Ku-Riang: Dekonstruksi Estetik Riak Ego dan Krisis Identitas dalam Ambiguitas Mozaik Digital : Mitologi Sangkuriang Generasi Moderen - Deden Maulana; I Made Gede Arimbawa; Anak Agung Gde Bagus Udayana; I Wayan Sujana (Kartala Virtual Studies, 2026)
Ancient mythologies of the Indonesian archipelago are frequently positioned as static didactic narratives. This study aims to recontextualize the legend of Sangkuriang into a new media art platform through an interactive digital mosaic installation. Employing a qualitative, practice-led research methodology, the name "Sangkuriang" is philosophically deconstructed into the conceptual framework of Sangka-Ku-Riang, a representation of the human ego's erroneous illusion of absolute control over reality and desire. This conceptual transformation is empirically articulated into visual computation parameters using the WebGL library, wherein the character's psychological dynamics are translated through fluctuations in fluid mosaic particle movement, geometric grid density, and lighting manipulation. The findings demonstrate that glitch art aesthetics specifically micro-stuttering and total system crashes effectively serve as semiotic signifiers to communicate the main character's identity crisis and raw destructive emotions. The final phase of form-setting into a mountain silhouette reflects a contemplative aesthetic sublimation that locks data chaos into a space of stability. Culturally, this visual articulation aligns with the Sundanese cosmology of darmaning satria, which asserts that human egoistic ambition must ultimately submit to macrocosmic cosmic laws. This study offers a novel method for conserving traditional heritage, transforming it into a living digital entity that adapts critically to contemporary technological advancement.